Has there been a change in the way of diagnosing the infertile couple? - Castillo, Juan (2014)
This article debates about the practical use of conventional methods for the evaluation of the infertile couple, and also explores the clinical impact of recently described ovarian reserve markers. Infertile couple work up is based on the evaluation of three main parameters: ovulation, Fallopian tubes patency and sperm quality. Progesterone level on the 21st day of menses, hysterosalpingography, and spermiogram are the best initial tools for infertility evaluation. But also, the ovarian reserve and uterine integrity must be evaluated; for such aim, antral follicle count or determination of antimullerian hormone together with transvaginal ultrasound supposes a great step forward to the correct evaluation of the infertile couple.